How gender, ethnicity, and college experiences affect Latinas' undergraduate college persistence - Diaz de Sabates, Gabriela (Kansas State University, 2014)
This qualitative case study examined how the intersection of gender, ethnicity, and college experiences affected five Latina undergraduate students' academic persistence in a predominately White, Research Extensive Midwestern State University. Latinas' gender, race, ethnicity, and college experiences influence their educational achievements directly. Because most research concentrates on understanding Latinas' educational experiences from a cultural deficit perspective, this research addressed the need to investigate Latinas' personal understanding of the challenges they face in college and their responses and coping strategies utilized to navigate their experiences and persist academically. Cultural Congruity was the theoretical framework for analysis and interpretation in this study because it contextualized the understanding of Latinas' culture of origin and its values in relation to the cultural values upheld by the university Latinas attend. The research utilized life narratives to understand the meaning the participants gave to their college experiences. Life narratives invent, reform, and refashion personal and collective identity for underrepresented people. Life narratives provided direct access to accounts of participants' lived experiences while identifying the ideologies and beliefs shaped by those experiences. The findings in this study identified the stereotypes, racism, obstacles, and support encountered by Latinas in college and at home. Further findings include: Impact and relevance that caring relationships and high expectations had on their academic persistence, Latinas' determination to be involved in college and give back to their parents and communities, and how academic effectiveness acted as a form of resistance for Latinas' college persistence. Four additional themes emerged: How self-efficacy was used by Latinas to redefine themselves in college, the changing effect that intellectually stimulating courses had on Latinas in college, their tenacity to succeed, and Latinas' identification of their fathers as feminist role models. Recommendations for practice and future research are addressed. The results contribute to the limited research on Latinas' persistence in higher education and the personal meaning that they give to the obstacles and support they encounter in college. Further, the findings defy the stereotypes attributed frequently to Latinas.
Keywords: College persistence; Cultural congruity; Ethnicity; Gender; Latinas; Life narratives; Curriculum Development (0727); Education, General (0515); Women's Studies (0453)